Introduction to the hospitality industry. (New Jersey : John Wiley & Son, Inc., 2006)
This book offers a comprehensive treatment of the entire hospitality industry, updated to reflect trends in the hospitality, foodservice, and travel/tourism industries.
The hospitality industry and you -- Forces affecting growth and change in the hospitality industry -- The restaurant business -- Restaurant operations -- Restaurant industry organization: chain, independent, or franchise -- Competitive forces in food service -- Issues facing food service -- On-site food service -- Lodging: meeting guest needs -- Hotel and motel operations -- Forces shaping the hotel business -- Competition in the lodging business -- Tourism: front and center -- Destinations: tourism generators -- The role of service in the hospitality industry.
Keywords: HOSPITALITY INDUSTRY